SUBALTERN STUDIES - Satyanarayana, P. (International Journal of Research -GRANTHAALAYAH, 2016)
This paper explores the roots of the term ‘Subaltern’. The form of literature is backed by the history from time to time. The participation of the tribes in revolutions against the then ruling agencies escapes from the history proper. The unwritten languages of the tribes are posing a challenge. They are undermined. The 80 languages have not been brought to the pages of constitution of India. A language spoken by 10, 000 people have to be recognized as a language. There is a dire necessity of the study of folklore. In the multicultural society there is a need for projecting the life-s style and culture of the tribal population. The human rights speak volumes of betterment and welfare of the tribals on the norms of equality, fraternity and liberty. The evaluation of Subaltern studies has been traced right from the past to the present context in the paper to the extent possible. Mahasveta Devi’s visison is presented along with illustrations of her reasoning. The need for emergence of trends is emphasized in view of the humanitarian outlooks. The Telangana and Andhra Pradesh states are taken up for tracing the subaltern element with a few episodes emanating from history and folklore. Thus the retrospects and the prospects gauged in the paper will justify the Subaltern Studies.